Unveiling the Determinants of Knowledge Sharing and Their Impact on Service Innovation Performance in the Government Sector - Rizky, Fajar; Altino, Iqbal Caraka; Sensuse, Dana Indra; Lusa, Sofian; Safitri, Nadya; Elisabeth, Damayanti (SAFE-Network, 2025)
Knowledge sharing serves as a fundamental driver of organizational innovation, particularly in enhancing public service quality, yet remains significantly underutilized in government institutions. Many public sector organizations fail to recognize the value of knowledge sharing due to its perceived long-term benefits and the absence of concrete evidence demonstrating its measurable impact on service innovation performance. This study examines the driving factors of knowledge sharing and its impact on service innovation performance in government organizations. Data was collected through an online survey targeted at National Civil Service Agency (Badan Kepegawaian Negara or BKN) employees. A total of 465 responses were obtained, which analysed using partial least squares structural equation modeling (PLS-SEM). This study demonstrates that organizational, individual, and technological factors play a significant role in the implementation of knowledge sharing. Most importantly, the research provides empirical validation that knowledge sharing behavior directly and substantially enhance service innovation performance - a relationship previously overlooked in public sector studies. By expanding the theoretical framework of Planned Behavior to incorporate these organizational, individual, and technological dimensions, this study offers public administrators compelling evidence to prioritize knowledge sharing initiatives while providing scholars with a more holistic understanding of innovation mechanisms in government contexts. Future studies should explore additional factors beyond the Theory of Planned Behavior that influence knowledge sharing, as well as other knowledge management dimensions affecting service innovation. Further research could also investigate impacts of knowledge sharing beyond innovation performance, such as organizational resilience or employee well-being in public sector contexts.